Link between Coulomb stress changes and seismic activation in the eastern Marmara sea after the 1999, Izmit (Turkey), earthquake. Issue 2 (28th February 2013) - Durand, Virginie; Bouchon, Michel; Karabulut, Hayrullah; Marsan, David; Schmittbuhl, Jean
Abstract : [1] We investigate the effect of dynamic and static stress changes produced by the 1999 Izmit earthquake, on four preexisting seismic clusters located in the eastern Marmara sea, beyond the western termination of the earthquake rupture. These four clusters show long‐lasting modifications in their seismicity rate. We observe that these seismic activity variations are related to stress changes. Dynamic stress pulses activate strike‐slip faulting instantaneously, but in the absence of a concomitant static Coulomb stress increase, this activation is short lived. Indeed, a large dynamic stress combined with a negative static Coulomb stress may result in an immediate activation followed by the occurrence of a seismicity shadow. In contrast, the activation of extensional clusters begins slowly and takes a few days to fully develop. It is also remarkably long lasting and does not follow a classical Omori decay. More than 10 years after the earthquake, the extensional clusters located near the termination of the rupture, where static stress and pressure changes were high, are still activated. Key Points: Seismogenic response to stress changes differ between strike‐slip and extension Static, dynamic and poro‐elastic stress changes all control seismicity Seismogenic responses to Izmit earthquake present some delay